Szkoła jako przestrzeń do zagospodarowania i eksperymentowania - Niewiński, Jakub (Tomorrow’s school? Tradition and (r)evolutions in education, 2023)
Although the Polish school continues the 19th-century model of Prussian education, there are alternative ideas appear on the educational map, e.g. in the form of free democratic schools which, apart from a pedagogical experiment, set new trends in the 21st century. The presented paper recalls the thoughts of the creators of alternative pedagogy: Maria Montessori, Rudolf Steiner and Kurt Hahn, but also shows the creative ferment of the pedagogy of hope – the Dutch school of peace and the grassroots movement of Schule im Aufbruch using the latest research from neurobiologists. The author of paper shares his experience and describes the pedagogical innovation that functioned for six years in the middle school. The interdisciplinary hybrid connected the formal education with non-formal activities and block teaching with the high autonomy of students in terms of class self-governance. The context for considering school is the analysis of the results of the Report on mental and physical well-being of young people (UNICEF).